Incarceration Length, Employment, and Earnings - Jeffrey R. Kling
This paper estimates effects of increases in incarceration length on employment and earnings prospects of individuals after their release from prison. I utilize a variety of research designs including controlling for observable factors and using instrumental variables for incarceration length based on randomly assigned judges with different sentencing propensities. The results show no consistent evidence of adverse labor market consequences of longer incarceration length using any of the analytical methods in either the state system in Florida or the federal system in California.